Representations, Analysis and Recognition of Shape and Motion from Imaging Data : 7th International Workshop, RFMI 2017, Savoie, France, December 17-20, 2017, Revised Selected Papers /: 7th International Workshop, RFMI 2017, Savoie, France, December 17-20, 2017, Revised Selected Papers. (2019) - Unknown
No abstract available